Experiences of Public Doctors on Managing Work Difficulties and Maintaining Professional Enthusiasm in Acute General Hospitals: A Qualitative Study - Luk, Andrew Leung; Yau, Adrian Fai To (Frontiers in Public Health, 2018)
Background: Overseas studies suggest that 10 to 20% of doctors are depressed, 30 to 45% have burnout, and many report dissatisfaction with work-life balance. A local study on public doctors showed that 31.4% of the respondents satisfied the criteria for high burnout. Young but moderately experienced doctors who need to work shifts appeared most vulnerable. This study aims to explore the experiences of those public doctors who have managed their work difficulties and maintained professional enthusiasm for references in medical education and continuing professional training. Method: Ten public doctors with reputation were invited respectively from 3 acute general hospitals for an in-depth interview. Interviews were audio recorded and transcribed. Content analysis was carried out to identify major themes in relation to the research questions. Results: Three themes emerging from difficulties encountered were 1) managing people, mostly are patients, followed by colleagues and then patients’ relatives; 2) constraints at work, include time and resources. 3) managing self with decision making within a short time. Three themes generating from managing work difficulties included 1) self-adjustment with practicing problem solving and learning good communication appeared more frequently, followed by maintaining a professional attitude and accumulating clinical experiences; 2) seeking help from others; 3) organizational support is also a theme though it is the least mentioned. Four themes emerging from maintaining work enthusiasm were 1) Personal conviction and discipline: believing that they are helping the needy, having the sense of vocation and support from religion; disciplining oneself by continuing education, maintaining harmonious family relationship and volunteer work. 2) Challenging work: different challenging natures of their job. 3)Positive feedback from patients: positive encounters with patients keep a connectedness with their clients. 4) Organization support: working with good colleagues and opportunity for continuous training. Conclusions: Some implications for medical education include developing good communication skill for medical students and junior doctors, preparing senior doctors to be mentors and exploring the motivating force of spirituality/religion. Key words: Work difficulties, professional enthusiasm, doctors’ burnout, physician’s resilience